Aesthetic Wisdom in Sundanese Traditional Proverbs: Exploring Heritage Value and Cultural Depth through Oral Artefacts - Ita Rodiah (2025)
This research examines Sundanese traditional proverbs as culturally embedded oral artefacts that embody aesthetic values, local wisdom and intangible cultural heritage within West Java’s Sundanese communities. Departing from conventional folkloristic and literary approaches that often treat proverbs as static texts, this study adopts a Barthesian semiotic framework, drawing on Roland Barthes’s theory of myth to analyze proverbs as dynamic signifying systems that naturalize cultural ideologies and encode inherited worldview. Through participatory ethnography over eighteen proverbs were collected through community interviews, oral storytelling and archival triangulation. Each proverb was examined not only in its linguistic form but as a mythic structure in Barthes’ sense, a second-order semiological system that transform cultural values into self-evident truths. Findings highlight that Sundanese traditional proverbs function as aesthetic-cultural systems, conveying harmony with nature, intergenerational respect, communal balance and resistance to cultural homogenization. By examining how these proverbs operate both semantically and ideologically, the study shows how they act as mythic speech that reinforces local identity and moral consciousness, while simultaneously adapting to contemporary cultural contexts. This re-framing challenges the treatment of proverbs as inert folklore and instead presents them as living, semiotic practices that play an active role in the negotiation of meaning, memory and cultural continuity. Ultimately, this study offers a novel methodological contribution by integrating aesthetic analysis with Barthesian semiotics to interrogate oral traditions within endangered linguistic communities. It argues for the urgent preservation and revalorization of such oral artefacts as part of broader efforts in cultural sustainability and intangible heritage protection. In doing so, the findings contribute not only to Sundanese cultural studies but also to wider interdisciplinary dialogue on language preservation, the aesthetics of local wisdom and the politics of representation in intangible heritage discourses.